2013
DOI: 10.1161/atvbaha.112.300663
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proinflammatory CD68 + Mannose Receptor Macrophages in Peroxiredoxin-1 Expression and in Abdominal Aortic Aneurysms in Humans

Abstract: Objective-Abdominal aortic aneurysms (AAAs), dilations of the infrarenal aorta, are characterized by inflammation and oxidative stress. We previously showed increased levels of peroxiredoxin-1 (PRDX-1) in macrophages cultured from AAA patients. The purpose of the study was to determine which subpopulation of macrophages is present in AAAs and is involved in upregulation of PRDX-1 in aneurysmal disease. Methods and Results-This study used immunohistochemistry with antibodies against CD68 and mannose receptor (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 47 publications
2
69
1
Order By: Relevance
“…Clearly, we observed a distinct morphology of macrophages M1 and M2 after 12 days of primary culture. As previously published, we verified by RT-PCR the presence of mRNA coding for TNF and IL1B in M1 macrophages and for MRC1 and CCL18 in M2 macrophages 14 (not shown).…”
Section: Representative Resultssupporting
confidence: 81%
“…Clearly, we observed a distinct morphology of macrophages M1 and M2 after 12 days of primary culture. As previously published, we verified by RT-PCR the presence of mRNA coding for TNF and IL1B in M1 macrophages and for MRC1 and CCL18 in M2 macrophages 14 (not shown).…”
Section: Representative Resultssupporting
confidence: 81%
“…[24]. In the adventitia, B lymphocytes and mast cells predominated, together with the proinflammatory CD68 + MR − (Mannose Receptor) macrophage subtype as previously shown [10] and neutrophils and T lymphocytes predominated, together with the anti-inflammatory subtype CD68 + MR + macrophages as previously shown in the intraluminal thrombus [10]. …”
Section: Resultsmentioning
confidence: 59%
“…Numerous inflammatory cells are involved in AAA formation and growth [7,9]. Recently, we showed that the two subtypes of macrophages, M1 with proinflammatory properties and M2, with anti-inflammatory properties are distributed differently in the aneurysmal wall [10]. Neutrophils are known to be involved in AAA [11] by recruiting other inflammatory cells [9] or producing MMPs such as MMP9 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical applications have been investigated by this method, including biomarker identification of breast cancer (Thakur et al, 2011;Zanni and Chan, 2011;Zhang et al, 2005), pancreatic ductal carcinoma (Shekouh et al, 2003), nasopharyngeal carcinoma (Cheng et al, 2008), hepatocellular carcinoma (Wong and Luk, 2012), and abdominal aortic aneurysms (Boytard et al, 2013). In this last study, Boytard and colleagues highlighted that CD68( + )MR(-) macrophages could contribute to aneurysmal pathology, on the basis of the analyses of 2DE separated proteins originated from different types of macrophages.…”
Section: Laser Capture Microdissection (Lcm)mentioning
confidence: 99%